Wearable solutions to enable humans to directly drive robot manipulators with force feedback - Teo, Marcus (2019)
This project aims to explore different ways to use wearable solutions for force feedback and intuitive robot teleoperation for its users, namely, to allow its user to control a robot arm without any prior technical expertise and to make it intuitive for them to control it. This would allow for a more widespread application of robotic systems into different industries. The wearable solutions include a virtual reality headset which is demonstrated with an HTC VIVE set and powered by Unity, and an inertial measurement unit (IMU) device which can be worn as a glove by the user. The HTC VIVE set includes two joysticks that the user can use to control the robot. By moving only one joystick by holding it in their hand, the user can control the position of the robot. The HTC VIVE controller provides force feedback to its user in terms of a vibration. The IMU glove works in the same manner, but this time the user wears it in the form of a glove. It provides force feedback to the robot system by mapping the bending of a user’s fingers to a gripper’s movement. To overcome the distance limitations faced by existing robot teleoperation systems, the use of virtual reality is also included, allowing the user to view the virtual environment as a digital mirror of the actual environment. Such a project has wide ranging applications such as bomb disposals, healthcare and handling of hazardous materials. This widens the user base to include non-technical people to control robot systems, allowing them to leverage the full potential of robotics systems.